Effects of climbing- and resistance-training on climbing-specific performance: a systematic review and meta-analysis - Stien, N.; Riiser, A.; Shaw, M. P.; Saeterbakken, A. H.; Andersen, V. (Biology of Sport, 2023)
The objective of this systematic review and meta-analysis was to examine the effects of climbing and climbing-and-resistance-training on climbing performance, and strength and endurance tests. We systematically searched three databases (SPORTDiscus, SCOPUS, and PubMed) for records published until January 2021. The search was limited to randomized-controlled trials using active climbers and measuring climbing performance or performance in climbing-specific tests. Data from the meta-analysis are presented as standardized difference in mean (SDM) with 95% confidence intervals (95% CI). Eleven studies are included in the systematic review and five studies compared training to a control group and could be meta-analyzed. The overall meta-analysis displayed an improvement in climbing-related test performance following climbing-specific resistance training compared to only climbing (SDM = 0.57, 95%CI = 0.24-0.91). Further analyses revealed that finger strength (SDM = 0.41, 95%CI 0.03-0.80), rate of force development (SDM = 0.91, 95%CI = 0.21-1.61), and forearm endurance (SDM = 1.23, 95%CI = 0.69-1.77) were improved by resistance-training of the finger flexors compared to climbing training. The systematic review showed that climbing performance may be improved by specific resistance training or interval-style bouldering. However, resistance-training of the finger flexors showed no improvements in strength or endurance in climbing-specific tests. The available evidence suggests that resistance-training may be more effective than just climbing-training for improving performance outcomes. Importantly, interventional studies including climbers is limited and more research is needed to confirm these findings.